Separatist Ireland and Germany, 1919-23 - O'Brien, Jennifer (Trinity College (Dublin, Ireland). Department of History, 2009)
This thesis examines Irish separatist foreign policy in 1919-23 through a case study of separatist activities in Germany. Separatists built on initial contacts and the work of local sympathisers in 1919-20 to establish a mission under John Chartres, which inaugurated a vigorous propaganda campaign in favour of Irish independence spearheaded by the bi-weekly Irische Bulletin. A consul, Charles Bewley, was also appointed to nurture commercial relations, while arms smugglers arranged two successful arms shipments m 1921-22. The thesis begins by outlining tentative links between separatists and the local German-Irish Society in 1919-20, examining the latter’s activities and its interpretation of Irish events. It then discusses the mission established in 1921, its institutional culture (personnel, finances, communications etc) and its contacts with influential figures in politics and the press. The thesis examines the mission’s propaganda campaign by examining the literature produced, particularly the bi-weekly Irische Bulletin, relating it to wider separatist ideology and propaganda and to German press coverage of Ireland.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin